High Serum Vitamin D Concentrations, Induced via Diet, Trigger Immune and Intestinal Microbiota Alterations Leading to Type 1 Diabetes Protection in NOD Mice - Martens, Pieter-Jan; Centelles-Lodeiro, Javier; Ellis, Darcy; Cook, Dana Paulina; Sassi, Gabriele; Verlinden, Lieve; Verstuyf, Annemieke; Raes, Jeroen; Mathieu, Chantal; Gysemans, Conny (Frontiers in Immunology, 2022)
The hormonally-active form of vitamin D, 1,25-dihydroxyvitamin D3, can modulate both innate and adaptive immunity, through binding to the nuclear vitamin D receptor expressed in most immune cells. A high dose of regular vitamin D protected non-obese diabetic (NOD) mice against type 1 diabetes (T1D), when initiated at birth and given lifelong. However, controversy exists on the level of circulating vitamin D (25-hydroxyvitamin D3, 25(OH)D3) needed to modulate the immune system in autoimmune-prone subjects and protect against T1D onset. We evaluated the impact of two doses of dietary vitamin D supplementation (400 and 800 IU/day), given to female NOD mice from 3 until 25 weeks of age, on disease development, peripheral and gut immune system, gut epithelial barrier function, and gut bacterial taxonomy. Serum 25(OH)D3 concentrations were 2.6- (400 IU/day) and 3.9-fold (800 IU/day) higher with dietary vitamin D supplementation compared to normal chow (NC), only the 800 IU/day vitamin D-supplemented diet delayed and reduced T1D incidence compared to NC. Flow cytometry analyses revealed an increased frequency of FoxP3+ Treg cells in mice receiving 800 IU/day vitamin D-supplemented diet. This vitamin D-induced increase in FoxP3+ Treg cells, also expressing the ecto-5’-nucleotidase CD73, only persisted at 25 weeks. At this time point, the frequency of IL-10-secreting CD4+ T cells was increased in all immune organs. High-dose vitamin D supplementation did not significantly modify the increased gut microbial diversity and richness over time observed in NOD mice receiving NC. The rise in alpha-diversity during maturation occurred especially in mice not progressing to hyperglycaemia. Principal coordinates analysis identified that both diet and disease status significantly influenced the inter-individual microbiota variation at the genus level. The abundance of the genera Ruminoclostridium_9 and Marvinbryantia gradually increased or decreased, respectively in faecal samples of mice on 800 IU/day vitamin D-supplemented diet compared to mice on 400 IU/day vitamin D-supplemented diet or NC, irrespective of disease outcome. In summary, dietary vitamin D reduced T1D incidence in female NOD mice at a dose of 800, but not 400, IU/day, and was accompanied by an expansion of Treg cells in various lymphoid organs and an altered intestinal microbiota signature.